Immunosuppression and HIV Infection: A Therapeutic Challenge - Sandra H Bridges; Margaret I Johnston; John J McGowan (Canadian Journal of Infectious Diseases)
The optimal use of biological response modifiers (BRMs) in human immunodeficiency virus (HIV)-related disease depends on knowledge of the molecular basis of the immune deficiencies and dysregulations that occur during the course of the infection; evidence for the role of viral products and cytokines in the suppression of immune function is discussed. Immunebased therapies are currently being explored alone and in combination with drugs targeted to HIV and associated opportunistic infections and malignancies. These therapies include hematopoietic growth factors for the management of drug toxicities, cytokines, antigen- and cell-based therapies, and synthetic immunomodulators. The entry of additional BRMs into clinical trials for HIV-disease can be facilitated by well-designed preclinical studies that address special problems related to the disease. including the need for concomitant therapy for the spectrum of disease manifestations encountered.